PENGARUH STRES, KEMAMPUAN AKADEMIK DAN KOMUNIKASI TERHADAP MOTIVASI MAHASISWA DALAM MENYELESAIKAN SKRIPSI (STUDI KASUS MAHASISWA JURUSAN TEKNIK ELEKTRO FAKULTAS TEKNIK UNIVERSITAS RIAU) - Wijaya Wardhana Abi; Sasmita Jumiati; Pramadewi Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze the effect of stress on student motivation in completing thesis, academic ability on student motivation in completing thesis and communication on student motivation in completing thesis. This research was conducted on students of the Department of Electrical Engineering, Faculty of Engineering, University of Riau with a population of 142 active students who are in the thesis completion stage by taking samples by accidental sampling (random sampling) and using the slovin formula. So, the samples in this study were 59 people. The data analysis technique used path analysis and multiple linear regression test. Based on the results of the analysis, it was found that stress had a significant negative effect on student motivation in completing thesis, academic ability had a significant positive effect on student motivation in completing thesis and communication had a significant positive effect on student motivation in completing thesis.Keywords: stress, academic ability, communication, student motivation in completing thesis